Subgroups and cliques in sport: A longitudinal case study of a rugby union team. (May 2017) - Wagstaff, Christopher R.D.; Martin, Luc J.; Thelwell, Richard C.
Abstract: Although subgroups and cliques are anecdotally referenced as salient factors in sport organizations, they have only recently received attention within sport psychology literature. This is surprising given the potential influence of subgroup behavior on group-related processes and team functioning. The present study employed a longitudinal, repeated interview case study design to examine competitive rugby players' awareness of subgroups and cliques, in addition to perceptions of their development, influence, and management over the course of a season. Findings indicated that players were not only able to articulate the nature of subgroups and cliques, but also to identify members of the various subunits. Both subgroup and clique membership and behavior were found to be fluid, develop over time, and be shaped by several organizational factors. Recommendations for the management of subgroups and cliques are provided, and the results are discussed in line with theoretical perspectives and practical applications. Highlights: This study offers a rigorous, longitudinal case study exploring subgroups and cliques in sport. A novel insight into athletes' acuity to awareness of subgroup membership, how it develops over time, and the influence of clique formation on teams. The conclusion imparts advice regarding the need for careful orchestration of sub-group monitoring and clique management.